Family’s Addressing Male and Female Batak Toba Tribe in Indonesia - Bambang Nur Alamsyah Lubis; Asnawi Asnawi (Randwick International of Education and Linguistics Science Journal, 2021)
This study deals with family addressing male and female in Batak Toba Language. The aim of this study to analyse the addresse of Batak Toba people in their social life. This study used descriptive qualitative as a method of reserach. This study was analyse the result of interview of Batak Toba people. The result, there were tweenty male and female addresses that was used by Batak Toba people in family interaction. This adresse is used to show the level of satus and to show respect to the oldest and love to the youngest family member.